The Choice of work for Outsourcing: Assessment Tools - D. A. Zhdanov (Управленческие науки)
The more extensive usage of outsourcing technology poses the challenge for enterprise management to identify possible benefits and problems of such cooperation. For this reason, the purpose of this study is to establish a procedure to determine the operations most suitable for outsourcing. The methodological base of the work consists of the new institutional economic theory provisions; situational analysis, mathematical and logical modeling of the identified relationships are used as methods of study. As a research result, the author detailed the elaboration of criteria that determine the effectiveness of the business processes transfer of the company to an external operator. As well as he specified the sequence of their application within a single procedure of the assessment. There are combined the specified factors in four directions, which characterize the key organizational and economic aspects of outsourcing. The specific feature of the approach is the consideration not only of traditional parameters related to the study of customer requests and the contractor capabilities, but also the nature of the relationship between the parties, as well as the state of the market environment in which the work is carried out. In conclusion, the author proposed an algorithm forexpress-assessment of the effectiveness of the transfer of operations to a third-party operator, based on the introduced approach. The results obtained will be useful to managers for identifying business development opportunities based on the outsourcing.